2015
DOI: 10.1155/2015/596126
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Depression and Drug Delivery with Food as an Effective Dosing Method: Evidences from Studies with Celecoxib and Dicholine Succinate

Abstract: Multiple models of human neuropsychiatric pathologies have been generated during the last decades which frequently use chronic dosing. Unfortunately, some drug administration methods may result in undesirable effects creating analysis confounds hampering model validity and preclinical assay outcomes. Here, automated analysis of floating behaviour, a sign of a depressive-like state, revealed that mice, subjected to a three-week intraperitoneal injection regimen, had increased floating. In order to probe an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
4
32
0
1
Order By: Relevance
“…Body weights during weeks 1‐6 and weight gain between these weeks were normalized to the mean values of wild‐type mice treated with vehicle (WT‐Veh). On the 6th week, 24‐hour food intake and 12‐hour water intake were evaluated as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weights during weeks 1‐6 and weight gain between these weeks were normalized to the mean values of wild‐type mice treated with vehicle (WT‐Veh). On the 6th week, 24‐hour food intake and 12‐hour water intake were evaluated as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Riluzole tablets (Sandoz, Almere, Netherlands) were crushed and dissolved in tap water, and its concentration was adjusted to the dosage of 8 mg/kg/day and daily water intake in CD1 mice . elecoxib‐containing food pellets were produced as described elsewhere, and drug concentration was adjusted to the dosage of 30 mg/kg/day and daily diet consumption.…”
Section: Methodsmentioning
confidence: 99%
“…A P‐NMR in vivo study demonstrated that DS preserved whole‐brain ATP decline in a rat model of global ischemia . Based on this and that DS demonstrated positive effects in animal models of brain disorders, including Alzheimer's disease, depression, chronic cerebral hypoperfusion, aging, and exposure to β‐amyloid peptide toxicity, it can be regarded as a drug candidate that normalizes IR functions . Its further clinical use can be promising in providing effective stimulation of IR‐mediated signaling while overcoming reported limitations with the use of insulin or insulin receptor sensitizers.…”
Section: Insulin Receptor Sensitizers As New Pharmacotherapy Of Neuromentioning
confidence: 99%
“…Sendo essa hipótese confirmada, esse conceito pode contribuir para futuros estudos de variáveis do estado depressivo. A literatura mostra a carência de modelos experimentais não invasivos de depressão [29].…”
Section: /9unclassified